Initial tadalafil and ambrisentan combination therapy in pulmonary arterial hypertension: cLinical and haemodYnamic long-term efficacy (ITALY study). Issue 1 (January 2018) - D'Alto, Michele; Romeo, Emanuele; Argiento, Paola; Paciocco, Giuseppe; Prediletto, Renato; Ghio, Stefano; Correale, Michele; Lo Giudice, Francesco; Badagliacca, Roberto; Greco, Alessandra; Vizza, Carmine Dario
Abstract : Aims: Initial combination therapy with ambrisentan and tadalafil (upfront therapy) offers clinical benefits in pulmonary arterial hypertension (PAH) and reduces the risk of clinical failure compared with monotherapy in naïve patients. The aim of study is to assess the efficacy of a 12-month upfront therapy with ambrisentan and tadalafil in improving haemodynamics in incident PAH patients. Methods: This is a multicentre retrospective analysis of real-world Italian clinical data in 56 patients with newly diagnosed PAH. Clinical evaluations, including demographics, medical history, WHO functional class, 6-min walk distance, and right heart catheterization, were collected from the patients' medical records at baseline and at 12-month follow-up. Results: At baseline, there were 16, 34, and 6 patients in WHO functional class II, III, and IV, respectively. Over a median follow-up of 12 months, 54 (96%) patients were still alive, 6 (11%) of whom received parenteral prostanoids. Ambrisentan–tadalafil combination was associated with significant improvements in WHO functional class (2.2 ± 0.8 vs. 2.8 ± 0.6, P  < 0.001, improved in 29 patients), exercise capacity (395 ± 123 vs. 353 ± 101 m, P  = 0.039), N-terminal probrain natriuretic peptide (528 ± 493 vs. 829 ± 620 pg/ml; P  = 0.009), and haemodynamics (right atrial pressure 7 ± 4 vs. 9 ± 5 mmHg, P  = 0.02; mean pulmonary artery pressure 45 ± 15 vs. 50 ± 13 mmHg, P  = 0.03; cardiac index 3.0 ± 1.0 vs. 2.5 ± 0.9 l/min/m 2, P  = 0.001; pulmonary vascular resistance 8 ± 4 vs. 11 ± 6 Wood units, P  = 0.001) compared with baseline. Conclusions: Initial combination therapy with ambrisentan and tadalafil offers clinical benefits and significant haemodynamic improvement in newly diagnosed PAH patients.